Developmental anomalies and other pathological lesions of the sternum in a medieval osteological sample - Farkas, Gyula L.; Józsa, László; Paja, László (Acta Biologica Szegediensis, 2004)
We cannot often read about the developmental anomalies of the sternum in paleopathological literature (Brothwell 1965; Tóth and Buda 2001); medical publications on anomalies resulting in chest deformity based on recent population are also rare (Keszler and Szabó 1996). Fractures and inflammation of the sternum are fairly infrequent, and the symptoms of porotic hyperostosis caused by increased red blood cell production are seldom detected in osteological samples. Some developmental anomalies (e. g. sternum fenestratum, alterations of the xiphoid process) do not influence the function or physiological form of the chest, while others may change the shape and diameter of the chest causing difficulties in breathing and in heart function. Some genetic diseases, through the malfunction of the production of the connecting tissues’ basic substantia and fibres, necessarily entail changes in the shape of the sternum. In individuals suffering from Marfan syndrome, sternum excavatum, while in individuals suffering from Hurler- and Morqio-syndrome (and other mucopolysaccharidosis cases), pectus gallinaceum can be observed. Other sternum anomalies resulting from non-genetic factors also seem to run in the family, though how they are inherited is not yet known. An anomaly called synchondrosis sternii develops during postnatal life, and means that the originally cartilaginous sternebrea do not become ossified, there remain synchondrosis between the parts even through the whole lifetime. This, however, does not cause abnormal chest movement. In some cases, the fracture of the sternum may lead to serious respiratory disfunction, and the healing of these injuries without any surgical intervention is not guaranteed. The development of pseudo-articulations may also cause abnormal chest movement. Osteomyelitis spreading to other organs may prove to be dangerous, even fatal.